THE INFECTION CAUSED BY ACINETOBACTER BAUMANNII IN THE INTENSIVE CARE UNITS OF A GENERAL HOSPITAL - L. L. Plotkin; I. V. Molchanova; P. G. Chumakov; M. Yu. Rakhmanov; A. Yu. Tyurin; Yu. M. Marchenko (Вестник анестезиологии и реаниматологии, 2018)
The objective of the study: to investigate the course of infection, caused by A. baumannii, in the patients in the intensive care units of a general hospital. Methods. The retrospective cohort study was conducted, which included 830 patients of the intensive care wards suffering from nosocomial infections caused by Acinetobacter baumanii. The bacterial diagnostics and drug susceptibility testing were performed using the analyzer of ADAGIO (Bio Rad, USA), Vitex 2 Compact 60 (bio Mariex, France) and the bacteriological analyzer for testing of sterile blood cultures of Bact Alar 3D60 (bio Mariex, France). As a result, certain specific features of this infection were identified: higher frequency of this disease in the patients with unfavorable co-morbid background (p = 0.042), prevailing lesions of abdomen (p = 0.04), skin and soft tissues (p = 0.02), frequent manifestations of septic shock (14%; p = 0.025) with a high mortality rate (16%; p = 0.025). Conclusions. 1. In 28% of cases, Acinetobacter baumannii accounts for the development of nosocomial infection in the patients staying in the intensive care ward. 2. Abdomen (18%), skin and soft tissues (8%) are most frequent sites where lesions caused by this infection are diagnosed. 3. The co-infection caused by A. baumannii most often develops in the patients with compromised co-morbid background (Charlson score makes 4.6 ± 0.3), which explains the severity of their state (APACHE II score makes 18.0 ± 1.6), development of organ failures (SOFA scores make 6.00 ± 0.05) and high frequency of septic shock (14%; p = 0.025). 4. The high mortality is typical of the course of the infection caused by A. baumannii, (16% versus 5.6%) in the patients with nosocomial infections caused by the other gram-negative bacteria.